In the Black Mirror: Youth Investigations into Artificial Intelligence - Lee, Clifford H; Gobir, Nimah; Gurn, Alex; Soep, Elisabeth (ACM Transactions on Computing Education, 2022)
Over the past two decades, innovations powered by artificial intelligence (AI) have extended into nearly all facets of human experience. Our ethnographic research suggests that while young people sense they can't "trust" AI, many are not sure how it works or how much control they have over its growing role in their lives. In this study, we attempt to answer the following questions: (1) What can we learn about young people's understanding of AI when they produce media with and about it?; and (2) What are the design features of an ethics-centered pedagogy that promotes STEM engagement via AI? To answer these questions, we co-developed and documented three projects at YR Media, a national network of youth journalists and artists who create multimedia for public distribution. Participants are predominantly youth of color and those contending with economic and other barriers to full participation in STEM fields. Findings showed that by creating a learning ecology that centered the cultures and experiences of its learners while leveraging familiar tools for critical analysis, youth deepened their understanding of AI. Our study also showed that providing opportunities for youth to produce ethics-centered interactive stories interrogating invisibilized AI functionalities, and to release those stories to the public, empowered them to creatively express their understandings and apprehensions about AI.